Factors affection degradation of barley straw in sacco and microbial activity in the rumeo of cows fed fibre-rich diets. lII. The amount of supplemental energy (Semiárida, 2020)
A basic diel composed of 76.2% untreated barley straw +23.8% grass hay was given to three non-Iactaling cows al 90% of ad Iibitum intake; the diel was supplemented with fishmeal to make the ration up to 12% protein on dry matter basis, a mineral-vitamin mixture and either 1.5 kg; 3.0 kg or 4.5 kg of rolled barley/cow x day in a Lalin Square designo The inclusion of rolled barley affected the degradabilily of DM, OM and individual components of the cell wall of barley straw incubated in nylon bags for up to 72 h. The higher the energy level of supplementation, the lower the digestion of the cell wall components. The amount of starch influenced rumen pH, ammonia and VFAs concentrations, ATP and protozoal numbers, but no treatment effect could be detected upon the outflow rale of Iiquid or particulate phases. The ATP and DNA concentrations found inside the nylon bags suggest the presence of an inactive or less active population towards the substrate after 24 h of incubation.Resúmenes de Trabajos presentados en otras publicaciones (por docentes de la UNLPam.) Publicado en Animal Feed Science Technology, 70: 225-238, 1998.
Keywords: energy; supplementation; straw degradation; rumen; cow